Physico chemical parameters of water of some selected areas of Tamirabarani river, Tirunelveli, Tamilnadu (International Journal of Scientific Research and Management (IJSRM), 2018)
In Tirunelveli and Thoothukudi districts Tamirabarani River is flowing continuously for 120km (24km in hilly terrain and 96km in plains) and drains into the Bay of Bengal at Punnaikayal village. In this present study, physico chemical parameters of some selected areas of Tamirabarani River water of Tirunelveli, was analyzed from 2013 to 2016. Seven sampling points were selected and the water samples were examined. The parameters such as chloride, sulphate, total alkalinity, calcium, magnesium and hardnesswere analyzed. Paper industrial waste, textile pollutants and temple waste are added to this point. These are the main sources of pollutants of Tamirabarani River. Tamirabarani is a main source of water supply to many towns which include Tirunelveli Corporation. In Tirunelveli corporation area the drinking water is not treated properly. Entire flow on the river has turbidity. The main aim of this paper is to analyze the various pollutants of Tamirabarani River by selecting seven different sites.